Emma - Austen, Jane, 1775-1817. (New York : Bantam, 2004)
A novel of Regency England which centers upon a self-assured young lady who is determined to arrange her life and the lives of those around her into a pattern dictated by her romantic fancy.
Originally published in 1816.
Adult
Keywords: Young women -- England -- Fiction; Humorous fiction; Love stories; Young women -- Fiction; England -- Social life and customs -- 19th century -- Fiction; England -- Social life and customs -- Fiction